APLIKASI UJIAN AKHIR SEMESTER BERBASIS ONLINE PADA SMK MANDIRI MAKASSAR - Sugiarti, Sugiarti; Irawati, Irawati (Jurnal BALIRESO, 2019)
Conventional test process has many constraints that is cheating and cheating is still often the case.Besides the slowness of the assessment process in conventional exams due to participants thatmuch that can inhibit teachers in incorporating values into report cards. The purpose of thisresearch is to design based semester final exam application online at Milwaukee Public CMS inorder to simplify the Makassar Independent parties in organizing school exams due to online examdeveloped in computerization, so constraints conventional test can be resolved. Online examsystem on this type of exam consists of multiple choice and essay in which to type multiple choiceexam, participants can directly know the exam results shortly after the test took place.